Loose ends in the differential diagnosis of IBS-like symptoms - Lindberg, Greger; Mohammadian, Ghazaleh (Frontiers in Medicine, 2023)
Two thirds of the patients we believed to have IBS in the 1970’s have since been possible to diagnose with treatable conditions like bile acid diarrhea, inflammatory bowel disease, microscopic colitis, celiac disease, disaccharide malabsorption, exocrine pancreatic insufficiency, or rare genetic variants. Despite advances in diagnostic techniques a substantial proportion of patients continue suffering from IBS-like symptoms that cannot be explained by current knowledge. Although it is likely that further research will reveal small but important subgroups of patients with treatable mechanisms for IBS-like symptoms, we propose that only two large groups remain for being addressed in the clinic: those with connective tissue disorders such as Ehlers-Danlos syndrome or hypermobility spectrum disorders and those with autism spectrum disorders. Patients with connective tissue disorders exhibit identifiable disturbances of gut motor function and possibly increased gut permeability as underlying mechanisms for IBS-like symptoms. Autism spectrum disorders pose a much more difficult problem in the clinic. Disturbances of perception combined with anxiety and excessive worry about signals from the gut can lead to an endless but futile search for something being wrong. The search can involve large numbers of care givers, no one understanding the patient’s suffering. Others may try to change their diet to lessen symptoms, only to find that almost all foods may cause worrying perceptions from the gut. Early recognition of autism spectrum disorders is essential for finding better ways to help patients with gastrointestinal and, as is often the case, extraintestinal symptoms.